2017
DOI: 10.4049/jimmunol.1600914
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T Cells Promote Myositis and Muscle Damage in Toxoplasma gondii Infection

Abstract: The coordination of macrophage polarization is essential for the robust regenerative potential of skeletal muscle. Repair begins with an inflammatory monocyte/pro-inflammatory macrophage (M1)-mediated phase followed by polarization to a pro-regenerative (M2) phenotype. Recently, regulatory T cells (Tregs) were described as necessary for this M1 to M2 transition. Here, we report that chronic infection with the protozoan parasite Toxoplasma gondii causes a non-resolving Th1 myositis with prolonged tissue damage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
64
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(75 citation statements)
references
References 50 publications
11
64
0
Order By: Relevance
“…However, paradoxical pathogenic roles for Tregs were reported in chronic muscle injury infected with Toxoplasma gondii . Jin et al showed that prolonged tissue damage was associated with persistent pro-inflammatory macrophage accumulation, whereas Treg ablation during this process rescued macrophage homeostasis and skeletal muscle fibre regeneration [26]. Thus, the key to interpreting the role of Tregs in muscle damage is the tissue environment established by the injury signal.…”
Section: Treg-mediated Repair At Multiple Tissuesmentioning
confidence: 99%
“…However, paradoxical pathogenic roles for Tregs were reported in chronic muscle injury infected with Toxoplasma gondii . Jin et al showed that prolonged tissue damage was associated with persistent pro-inflammatory macrophage accumulation, whereas Treg ablation during this process rescued macrophage homeostasis and skeletal muscle fibre regeneration [26]. Thus, the key to interpreting the role of Tregs in muscle damage is the tissue environment established by the injury signal.…”
Section: Treg-mediated Repair At Multiple Tissuesmentioning
confidence: 99%
“…Chronic infections of the skeletal muscle have previously been shown to severely alter the tissue immune landscape and compromise immune-regulatory networks (7, 1820). Toxoplasma gondii is an obligate intracellular parasite capable of establishing a chronic infection in the CNS and striated muscle tissues (21).…”
Section: Introductionmentioning
confidence: 99%
“…A robust interferon-gamma (IFNγ)-mediated immune response is necessary to control infection (21). Recently, we showed chronic skeletal muscle infection with Toxoplasma gondii drastically alters skeletal muscle immunity and leads to long-term muscle damage and myositis (18). Tregs decrease in frequency and also highly express the Th1-lineage specific transcription factor Tbet in infected skeletal muscle (18).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations